Romans 1:18-32 amidst the gay-debate: Interpretative options - Punt, J. (HTS teologiese studies, 2007)
The prominence of Romans 1:18-32 in the gay-debate is the subject of various and wide-ranging opinions as far as the most adequate interpretation of this passage. This contribution puts the debate about the text into perspective by surveying some recent alternative opinions on its meaning. It is established that two particular matters are most important in Romans 1:18-32 and the past and current debate on its interpretation: the argument according to “nature” and the nature of the infringement or error (Rm 1:27).